(untitled) (CAHIERS MAGELLANES-NS, 2024)
This study validates and expands upon previous findings regarding two novel compounds isolated from Withania somnifera, emphasizing their potential therapeutic applications. The significance of this work lies in its comprehensive in silico toxicity analysis, which assesses the safety and efficacy of these compounds. Using ACD/ChemSketch and OpenBabel software, the chemical structures of the compounds were prepared and converted into SMILES format for further analysis. The PASS prediction software indicated that Compound 1 exhibits significant biological activities, including strong potential as a growth hormone agonist and antineoplastic agent, while Compound 2 also shows promising activity as an antineoplastic and CYP3A substrate. Drug-likeness assessments using SwissADME revealed that both compounds conform to multiple drug-likeness rules, with Compound 1 demonstrating slightly better properties than Compound 2. Furthermore, ADMET analysis indicated favorable pharmacokinetic profiles for both compounds, with distinct advantages in absorption and distribution characteristics. These findings suggest that both compounds possess significant therapeutic potential, warranting further investigation for their development as drug candidates.